An Unusual Metastasis of a Transglottic Squamous Cell Carcinoma to the Forearm. (3rd June 2013) - Albeyatti, Abdullah Dafir; Kwasnicki, Richard Mark; Siau, Derrick; de Carpentier, John
Abstract : Introduction . Each year around 2, 200 people in the UK are diagnosed with laryngeal SCC (Office of National Statistics 2009). Compared to pharyngeal carcinoma, it is a highly curable disease with a survival rate of around 60% for all stages and all forms of treatment. Case Presentation . We present the case of a 60-year-old man with a previously treated T4 N2c transglottic squamous cell carcinoma (SCC), who developed an isolated swelling in the extensor compartment of his right forearm at 6 months after radical laryngectomy with bilateral neck dissection. Fine needle aspiration of the forearm lesion revealed SCC consistent with a metastasis from the laryngeal primary. MRI revealed that the lesion was confined to the muscle. Initial staging CT showed no distant metastases or signs of advanced disease, including no evidence of axillary nodal involvement. Conclusion . This case is therefore unusual, as one of only 2 cases reported in the scientific literature of isolated distant muscular metastasis from a laryngeal squamous cell carcinoma. We conclude that any muscular swelling, in the setting of previous head and neck malignancy, should be treated with a high degree of suspicion for metastasis and investigated promptly.